Morocco : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2003)
This Report on the Observance of Standards and Codes (ROSC) data module provides a review of Morocco's data dissemination practices against the IMF's General Data Dissemination System (GDDS), complemented by an in-depth assessment of the quality of the national accounts, consumer price index, producer price index, government finance, monetary, and balance-of-payments statistics. The assessment reveals that Morocco generally exceeds the GDDS recommendations on periodicity and timeliness for its macroeconomic statistics. For most data categories currently disseminated, Morocco meets the periodicity prescriptions of the Special Data Dissemination Standards.